Animal resource exploitation in the northern Guanzhong region during the mid-to-late Holocene: A zooarchaeological case study of the Xitou site - Wang, Qianwen; Liu, Kexin; Zhai, Linlin; Liu, Bin; Sun, Han; Li, Yue (Frontiers in Earth Science, 2023)
Zooarchaeological approach has been effective in providing insights into human subsistence practices, which laid essential economic foundation for social, cultural, and political developments in the past. The Guanzhong region in northern China played a crucial role in the origins and evolution of ancient Chinese civilization. Previous research on subsistence economies of ancient societies in the Guanzhong region, human exploitation of animal resources in particular, has largely focused on the late Neolithic period or the Bronze Age. Insufficient work has been done for historical periods post-dating the end of the first millennium BCE. There is also a dearth of research on the long-term chronological changes. Here, we present a preliminary analysis of animal remains from the Nantou Locale of the Xitou site, a large settlement located in the northern Guanzhong region. Results show that pigs played a dominant role in the site’s animal economy during the Neolithic Yangshao and Longshan periods (ca. 5000–2000 BCE). The growing importance of cattle and caprines was documented for the Bronze Age Western Zhou period (ca. 11th-8th centuries BCE). In the Han-Tang periods (ca. second century BCE-tenth century CE), pigs regained their significance in local subsistence practices. Differences in the strategies for animal resource exploitation were possibly associated with changing social and environmental factors. Alongside other relevant archaeological evidence, our zooarchaeological data demonstrate the contribution of diversified animal use strategies to sustained development of subsistence economy in the northern Guanzhong region across millennia. The examination of long-term human-animal interactions in the Guanzhong region allows for a better understanding of changing economic, social, and political landscapes in ancient China.